PERANCANGAN SISTEM KELISTRIKAN PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) OFF-GRID DI DUSUN KODAMRAA DESA ROHMONI KECAMATAN PULAU HARUKU - Jihan Amelia Wasahua; Lory Marcus Parera; Marselin Jamlaay (JURNAL SIMETRIK, 2026)
This study aims to design an Off-Grid Solar Power Plant (PLTS) system in Kodamara Hamlet, Rohomoni Village, Pulau Haruku District, which is not yet connected to the PLN electricity grid. This PLTS is designed to utilize solar energy as a renewable energy source. The study began with data collection regarding daily energy consumption and location characteristics. This data was then processed to calculate the daily energy load and optimal system capacity. The analysis results show that the total daily energy requirement reaches 16,452 Wh with a peak load of 2,582 W. The designed PLTS system consists of 16 350 Wp monocrystalline solar panels, 2 units of 75V/15A MPPT Solar Charge Controllers (SCC), 18 units of 48V/1000 Ah OpzV batteries combined in parallel, and 3 units of 5000W inverters. This design is considered feasible to provide an independent and sustainable electricity supply, as well as contributing to improving the quality of life of the people in Kodamara Hamlet through the use of environmentally friendly solar energy. Keywords: Off-Grid, Solar Energy, System Planning, Peak Sun Hour